Reimagining Space: Developing a Museum-Based Local Instructional Theory for Spatial Literacy in Elementary Geometry - Dina Octaria; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Cecil Hiltrimartin (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Spatial literacy is a key competency in elementary geometry. However, students often face difficulties in visualization, spatial reasoning, and spatial communication, particularly in learning cubes and cuboids. Common challenges include visualizing nets, understanding volume as layered space, and using formal spatial terminology. This study aims to develop a local instructional theory (LIT) on the volume and surface area of cubes and cuboids to strengthen spatial literacy through a culturally grounded learning trajectory situated in the Sultan Mahmud Badaruddin II Museum. It involved 44 fifth-grade students (aged 10-11) and employed a validation study design consisting of preparing for the experiment, design experiment (pilot and teaching experiments), and retrospective analysis. Data were collected through classroom observations, video recordings, student worksheets, miniature products, and group discussions. The data were then analyzed qualitatively using triangulation. Findings reveal recurring misconceptions, such as incorrect cube nets, interpreting volume as a two-dimensional, conflating surface area and volume, and reliance on informal language. Students’ learning progressed from contextual exploration to formal representation using manipulatives, teacher scaffolding, and Augmented Reality (AR). The resulting LIT is defined by three principles: the integration of manipulatives and AR, an emphasis on inter-dimensional relationships, and the enhancement of formal spatial communication within a Pendekatan Matematika Realistik Indonesia (PMRI) and Project-Based Learning (PjBL) framework.